2001
DOI: 10.1007/s004670100617
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone therapy in chronic renal failure induces catch-up of head circumference

Abstract: Growth of head circumference was studied along with height, weight, and body mass index (BMI) in 21 prepubertal patients with chronic renal failure (CRF) before and during recombinant human growth hormone (rhGH) treatment. CRF was present from birth in 15 patients, in the 6 others it was acquired and existing for at least 1 year. Five patients were on chronic dialysis, and 16 children were on conservative treatment with a median glomerular filtration rate of 17 ml/min per 1.73 m2 at the start of rhGH therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several studies detail the effects of recombinant human growth hormone (rhGH) therapy in renal conditions and most deal with the effect of rhGH therapy on children who have end-stage renal disease (ESRD) or on those who are on dialysis or who are post renal transplant [1,2,3,4,5]. This is the first report of rhGH therapy in growth-retarded children with autosomal recessive polycystic kidney disease (ARPKD) who have mild-to-moderate renal dysfunction.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies detail the effects of recombinant human growth hormone (rhGH) therapy in renal conditions and most deal with the effect of rhGH therapy on children who have end-stage renal disease (ESRD) or on those who are on dialysis or who are post renal transplant [1,2,3,4,5]. This is the first report of rhGH therapy in growth-retarded children with autosomal recessive polycystic kidney disease (ARPKD) who have mild-to-moderate renal dysfunction.…”
Section: Introductionmentioning
confidence: 97%
“…Early research indicated rather poor developmental outcomes for children with chronic kidney disease (CKD) during infancy, with the incidence of developmental delays estimated at 60% to 85% (Bale, Siegler, & Bray, 1980;Baluarte, Gruskin, Hiner, Foley, & Grover, 1977;Bird & Semmler, 1986;Bock et al, 1989;McGraw & Haka-Ikse, 1985;Polinsky, Kaiser, Stover, Frankenfield, & Baluarte, 1987;Rotundo et al, 1982;Warady, 2002). Neurodevelopmental delays in infants and preschool children with CKD were linked to a number of neurologically based conditions including microcephaly, seizures, mental retardation, reduced growth rates, impaired hemispheric maturation, and abnormal electrophysiological findings (Bock et al, 1989;Kari, Gonzalez, Ledermann, Shaw, & Rees, 2000;McGraw & Haka-Ikse, 1985;Polinsky et al, 1987;Rotundo et al, 1982;Van Dyck & Proesmans, 2001). In addition, early malnutrition, aluminum toxicity, hypertension, and anemia were also associated with developmental delay in patients with childhood CKD (Andreoli, Bergstein, & Sherrard, 1984;Conley, 1987;Lande, Kaczorowski, Auinger, Schwartz, & Weitzman, 2003;Marsh et al, 1991;National Kidney Foundation [NKF], 2001;Sedman, Miller, Warady, Lum, & Alfrey, 1984;Sedman, Wilkening, Warady, Lum, & Alfrey, 1984;Warady, 2002;Winick, 1969).…”
mentioning
confidence: 99%
“…In the early nineties, the multicenter, randomized, double-blind, placebo-controlled study of Fine et al (36), showed that rhGH therapy could significantly improve the growth of children with CKD. Clinical studies (18,23,(39)(40)(41)(42)(43) demonstrated the safety and efficacy of rhGH therapy in promoting height gain in children with CKD on dialysis or after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Kidney Disease (CKD) in pediatric and adult patients is characterized by a progressive decline in kidney function, classified according to the Kidney Disease: Improving Global Outcomes (KDIGO) in a system based primarily on glomerular filtration rate (eGFR, ml/min/1.73 m 2 ) and on proteinuria (1). The classification consists of 5 stages based on a decreasing of eGFR: G1 normal or high (≥ 90); G2 mildly decreased (60-89); G3a mildly to moderately decreased (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59); G3b moderately to severely decreased (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44); G4 severely decreased (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and G5 kidney failure (≤ 15, or dialysis) (1). According to these Guidelines, CKD should be established based on kidney function and damage expressed as eGFR, irrespective of...…”
Section: Introductionmentioning
confidence: 99%